Pengembangan Pembelajaran Pendidikan Agama Islam (Studi Penelitian Kualitatif tentang Mutu Pembelajaran PAI di SMK PGRI 1 Ponorogo) - Arifin Wahyudin Fatkhurahman Syah; An Nisa Bintang Kurniasari; Alif Binti Nur Nikmah; Astrid Tiara Sandra; Bayu Bintang Saputra; M. Irsyad Khairillah Ibnu Sulaeman; Nurul Malikah (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the quality of Islamic Religious Education (PAI) learning at SMK PGRI 1 Ponorogo and identify development strategies applied to improve learning effectiveness. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observations, and document analysis such as syllabus and lesson plans. The results showed that the development of PAI learning was carried out by utilizing interactive methods, using appropriate learning media, and strengthening teachers' competencies through continuous training. However, the research also found some obstacles, such as limited supporting facilities and lack of student learning motivation. To overcome this, the school conducted a collaborative program between teachers, students, and related parties to create a more conducive learning environment. This study confirms the importance of developing PAI learning integrated with character values to support the achievement of educational goals. The findings provide practical recommendations for schools in improving the quality of PAI learning, as well as a reference for further research in the field of religious education.